Aerosol indirect effects from ground‐based retrievals over the rain shadow region in Indian subcontinent. Issue 5 (14th March 2016) - Harikishan, G.; Padmakumari, B.; Maheskumar, R. S.; Pandithurai, G.; Min, Q. L.
Abstract: Aerosol‐induced changes in cloud microphysical and radiative properties have been studied for the first time using ground‐based and airborne observations over a semiarid rain shadow region. The study was conducted for nonprecipitating, ice‐free clouds during monsoon (July to September) and postmonsoon (October) months, when cloud condensation nuclei (CCN) concentrations over the region of interest increased monotonically and exhibited characteristics of continental origin. A multifilter rotating shadowband radiometer and microwave radiometric profiler were used to retrieve the cloud optical depth and liquid water path (LWP), respectively, from which cloud effective radius (CER) was obtained. CER showed wide variability from 10–18 µm and a decreasing trend toward the postmonsoon period. During monsoon, the estimated first aerosol indirect effect (AIE) increased from 0.01 to 0.23 with increase in LWP. AIE at different super saturations (SS) showed maximum value (significant at 95%) at 0.4% SS and higher LWP bin (250–300 g/m 2 ). Also, statistically significant AIE values were found at 0.6% and 0.8% SSs but at lower LWP bin (200–250 g/m 2 ). The relationship between CCN and CER showed high correlation at 0.4% SS at higher LWP bin, while at higher SSs good correlations were observed at lower LWPs. Data combined from ground‐based and aircraft observations showed dominance of microphysical effect at aerosol concentrations up to 1500 cm −3 and radiative effect at higher concentrations. This combined cloud microphysical and aerosol radiative effect is more prominent during postmonsoon period due to an increase in aerosol concentration. Key Points: High AIE observed over the rain shadow region can also be one of the causative factors for rainfall deficiency AIE is highly variable with CCN super saturation along with available cloud LWP Combined cloud microphysical‐aerosol radiative effects is prominent during postmonsoon period